Attitudes and beliefs of parents about routine childhood vaccination in Greece. Issue 9 (2nd September 2021) - Gkentzi, Despoina; Tsagri, Charalampia; Kostopoulou, Eirini; Fouzas, Sotirios; Vantarakis, Apostolos; Dimitriou, Gabriel; Varvarigou, Anastasia
ABSTRACT: Vaccine hesitancy remains one of the 10 major global threats as per the WHO report in 2019. The aim of the present study is to assess attitudes and perceptions of vaccine hesitant parents in Greece with a view to implementing strategies to increase vaccine uptake. A cross-sectional questionnaire-based prospective survey was conducted between September 2019 and June 2020 on parents of children attending primary education in the city of Patras in Western Greece. Data on parental attitudes and beliefs about vaccinations were collected and analyzed. Multivariable logistic regression was used to investigate factors associated with vaccine uptake. Out of 2154 distributed questionnaires, 1227 were completed and returned (response rate 56.9%). The main vaccine information source for Greek parents was their primary care pediatrician (90.8%). Doubts still exist amongst approximately one-third of them (33.5%) regarding a possible relationship between vaccines and autism. Of note, 44% of the study participants believe that unvaccinated children could attend school. 84.6% of the parents in our cohort admitted that they had fully vaccinated their children. In the multivariable analysis, marital status ( p < .002) and Greek nationality ( p < .001) were found to be the most significant determinants of vaccine uptake. Overall, we found that the percentage of parents in Greece that are vaccine hesitant is small yet not negligible. Based on our results, targeted public health interventions should particularly focus on single parents and those with non-Greek nationality. Training healthcare professionals to provide adequate information is crucial to clarify misperceptions.